A changing didacticism : the development of South African young adult fiction from 1985 to 2006 - Williams, Jenna Elizabeth (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2009)
This thesis endeavours to establish how political transformation in South Africa has impacted on the didactic function of locally produced young adult fiction between the years of 1985 and 2006. To this end, a selection of young adult novels and short stories are examined in relation to the time period during which they were written or are set, namely the final years of apartheid (from 1985 to the early 1990s), the period of transition from apartheid to democracy (approximately 1991 to 1997), and the early years of the twenty-first century (2000 to 2006). Chapter One provides a brief overview of publishing for the juvenile market in South Africa over the last century, noting how significant historical and political events affected both the publishing industry itself and the content of children's and young adult literature. This chapter also adumbrates the theoretical foundations of the study. The second chapter examines a selection of texts either written or set during the final years of the apartheid regime. This chapter establishes how authors during this period challenged notions of racial inequality and undermined the policies of the apartheid government, with varying degrees of success. The authors' methods in encouraging their (predominantly white) readers to question apartheid ideology are also interrogated. Those novels written after, but set during, the apartheid era are examined with the aim of determining their authors' didactic objectives in revisiting this period in their novels. Chapter Three explores how authors writing during the transition period aimed to encourage readers to participate in the building of a 'rainbow nation,' by portraying idealised modes of relating to the racial 'other.' While some of the authors examined in this chapter are optimistic, and even naïve, in their celebration of a newly established democracy, others are more cautious in suggesting that decades of oppression and separation can so easily be overcome. Chapter Four demonstrates how the freedoms afforded by a democratic society have prompted young adult authors to explore the possibilities of adapting the sub-genre of the teenage problem novel to suit a distinctly South African context. While some of these texts are not overtly didactic in nature, they confront the unique issues faced by a generation of South African teenagers raised in a democratic society, and in some cases challenge readers to reconsider their approach to such issues.
Keywords: Didactic fiction, English -- History and criticism; Young adult fiction, South African -- History and criticism; South Africa -- In literature; South Africa -- Politics and government